Understanding How Green Space Naturalness Impacts Public Well-Being: Prospects for Designing Healthier Cities - Bressane, Adriano [UNESP]; Silva, Mirela Beatriz [UNESP]; Goulart, Ana Paula Garcia [UNESP]; Medeiros, Líliam César de Castro [UNESP] (MDPI, 2024)
Statement of problem: Urbanization has brought significant advancements in human well-being; however, it poses challenges to urban green spaces (UGSs), affecting environmental quality and public health. Research gap: Previous studies have established the importance of UGSs for urban well-being but have not sufficiently explored how the naturalness of these spaces—ranging from untouched natural areas to human-designed landscapes—affects mental health outcomes in the context of developing countries, particularly Brazil. Purpose: This study aimed to bridge the research gap by investigating the relationship between the degree of naturalness in UGSs and mental health among residents of Brazilian metropolitan areas. Method: Data were collected through an online survey involving 2136 respondents from various Brazilian urban regions. The study used Welch’s ANOVA and Games–Howell post hoc tests to analyze the impact of UGS naturalness on mental health, considering depression, anxiety, and stress levels. Results and conclusions: The findings revealed that higher degrees of naturalness in UGSs significantly correlate with lower levels of mental distress. These results underscore the necessity of integrating natural elements into urban planning to enhance public health. Practical implications: Urban planners and policymakers are encouraged to prioritize the preservation and creation of naturalistic UGSs in urban environments to improve mental health outcomes. Future directions: Further research should explore the specific attributes of naturalness that most contribute to well-being and examine the scalability of these findings across different cultural and environmental contexts.
Keywords: mental health; naturalness; urban green spaces; urban planning